Formation et information-communication. Rapport final - Tome 2Training and information dissemination: Final report - Volume 2 of the Burkina Faso irrigation management project - International Irrigation Management Institute (International Irrigation Management Institute, 1997)
Synthesis report of the training and information dissemination activities carried out by the Burkina Faso Irrigation Management Project.